Impoliteness Strategies in the Comment Section of Donald Trump's Instagram Account - Ratu Shafira Nurfitria; I Dewa Putu Wijana (CV. Creative Tugu Pena, 2025)
Impoliteness in digital communication often manifests through provocative remarks and direct attacks, particularly in political contexts. This study investigates impoliteness in the comment sections of Donald Trump’s Instagram videos, focusing on the ways global audiences respond to his posts. The research aims to identify the types and functions of impoliteness expressed by users. Employing a qualitative descriptive method, the study analyzes comments collected from one of Trump’s Instagram videos using documentation and note-taking techniques. The data were examined through Culpeper’s theory of impoliteness, which categorizes strategies based on their forms and functions. The findings reveal four types of impoliteness strategies: bald-on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm or mock politeness. Notably, no evidence was found for the strategy of withholding politeness, which is typically observed in face-to-face communication but is less detectable in asynchronous platforms such as Instagram. In terms of functions, the analysis identified three distinct forms: affective impoliteness, coercive impoliteness, and entertaining impoliteness. This study demonstrates that impoliteness on social media is not merely a reflection of hostility but can also serve expressive, persuasive, and entertaining purposes. The findings highlight how global audiences employ impolite strategies to convey emotions, influence discourse, and engage with political figures. By situating impoliteness within digital political communication, this research contributes to the broader understanding of language use in online interaction and its impact on public perception of political leaders